Disaster, relocation, and resilience: recovery and adaptation of Karamemedesane in Lily Tribal Community after Typhoon Morakot, Taiwan. (14th March 2020) - Taiban, Sasala; Lin, Hui-Nien; Ko, Chun-Chieh
ABSTRACT: After Typhoon Morakot struck Taiwan in the summer of 2009, government officials relocated the indigenous village communities of Kucapungane, Adiri, Karamemedesane, Kinulane, Dawadawan and Tikuvulu into sub-montane, permanent housing. Because villagers were accustomed to living in mountainous areas, they encountered many challenges while adapting their lifestyle and culture into a new setting. During the relocation process, government and post-disaster relief agencies disregarded, oversimplified, and concealed social vulnerability. Can indigenous communities recover from typhoon damage and continue to pass down their culture? Using in-depth interviews and participant observation, this research examined how Karamemedesane villagers organised and reconstructed themselves using their land for farming practices, culture, rituals, and livelihoods following the government-forced, community migration. The source of resilience for Karamemedesane turned out to be the cultivation of red quinoa, a traditional food crop. Villagers rediscovered the cultural value of food through small changes in farming practices and knowledge, social network and social learning, leadership, and innovation-aided recovery that resulted in establishing the Academy of Special Rukai Crops. Results suggested that post-disaster policies for indigenous communities should be land-based and culturally relevant to promote transformability.